Hyperoxidation of ether-linked phospholipids accelerates neutrophil extracellular trap formation. Issue 1 (December 2017) - Yotsumoto, Satoshi; Muroi, Yuito; Chiba, Tatsuya; Ohmura, Rio; Yoneyama, Maki; Magarisawa, Megumi; Dodo, Kosuke; Terayama, Naoki; Sodeoka, Mikiko; Aoyagi, Ryohei; Arita, Makoto; Arakawa, Satoko; et al.
Abstract Because neutrophil extracellular trap (NET) formation is involved in the pathology of a wide variety of diseases, NET-regulating compounds are expected to be useful for the therapies of these diseases. In this study, we identified sulfasalazine (SSZ) as a potent enhancer of NET formation bothin vitro andin vivo . Although SSZ did not increase the amount of ROS generated, it accelerated the generation of ether-linked oxidized phospholipids, such as PE (18;1e/15-HETE) and PC (16;0e/13-HODE). Trolox, but not 2-ME, effectively suppressed lipid oxidation and NET formation that were induced by SSZ. SSZ is known as a potent inducer of ferroptosis in cancer cells by inhibiting xCT, a component of the cystine transporter. However, we found that SSZ accelerated NET formation in an xCT-independent manner. Structure-activity relationship studies revealed that the sulfapyridine moiety of SSZ plays a central role in enhancing NET formation. Furthermore, we found that two additional sulfonamide and sulfone derivatives possess NET-inducing activity by accelerating lipid oxidation. These results indicate that the hyperoxidation of ether-linked phospholipids is a key mechanism for accelerating NET formation.